Association of Preoperative Cerebrospinal Fluids Parameters With Early Shunt Obstruction in Patients With Post-hemorrhagic Hydrocephalus Treated by Lumboperitoneal Shunt - Sun, Tong; Cui, Wenyao; Chen, Siyang; Yuan, Yikai; Yang, Jingguo; Zhou, Yicheng; Li, Xuepei; Yu, Hang; You, Chao; Guan, Junwen (Frontiers in Neurology, 2021)
Background: Early shunt obstruction (SO) remains the most common cause of lumboperitoneal shunt (LPS) failure. Although there is anecdotal evidence that the level of cerebrospinal fluid (CSF) parameters might affect shunt performance, its association with early LPS obstruction in adults with post-hemorrhagic hydrocephalus (PHH) is unclear. Methods: The retrospective study was performed by reviewing the adults with PHH treated by LPS from years 2014 to 2018. We included patients with CSF samples analyzed within 1 week prior to shunt insertion or at the time of shunt insertion. Baseline characteristics of each patient were collected. The primary outcomes were the incidence rate and associated factors of SO occurring within 3 months of shunt placement. The secondary outcomes included scores on the National Institute of Health Stroke Scale (NIHSS) and Evans Index at discharge. Results: A total of 76 eligible patients were analyzed, of whom 61 were obstruction-free and 15 were early SO. The overall rate of early SO was 15.6%. The RBCs count and nucleated cells count in preoperative CSF were actually higher in patients with early SO, compared to patients in the control group. Multivariate analysis identified RBC elevation (>0 × 106/L; OR: 10.629, 95% CI: 1.238–91.224, p = 0.031) as a dependent risk factor for early SO. NIHSS dramatically decreased at discharge while the alteration of ventricular size was not observed. Conclusions: This study suggested that the presence of RBCs in preoperative CSF was associated with early SO in patients with PHH treated by LPS.